The Emigrant Experience : Songs of Highland Emigrants in North America - MacDonell, Margaret, 1920- (Book collections on Project MUSE., 1982)
Every man has a story to tell and this was no less true of the hundreds of emigrants from the Highlands and the Hebrides who crossed the Atlantic from the late eighteenth century to the early twentieth century to settle in North America. This selection of Scottish Gaelic songs brings to light the revealing and often touching poems of some twenty such emigrants. Focusing on themes of emigration and exile, their subjects range from the biblical motif of liberation from tyranny (pre-destined by the Creator who provided a land of bounty across the seas), to the happier future anticipated for his daughter by a loyalist fugitive in North Carolina; from a sense of security on the part of a clergyman settled in Pictou County after the disruption in his homeland, to the disenchantment of an emigrant to Manitoba who longed to move on to North Dakota. Their tone may be lyrical, elegaic, or satirical. Songs from various parts of the new world - the Carolinas, Nova Scotia, Prince Edward Island, Ontario, and the Canadian west - are included in Gaelic with a facing English translation. A short biography of each bard prefaces the selections attributed to him or her. Detailed notes provide a guide to sources and variant texts, elucidate obscure passages, and define the social and cultural context in which the songs originated. An appendix reproduces the tunes for nine of these songs. This is a book that will inform and entertain both the specialist and the general reader.